"Are You Sure?": Lapses in Self-Reported Activities Among Healthy Older Adults Reporting Online. (June 2016) - Wild, Katherine V.; Mattek, Nora; Austin, Daniel; Kaye, Jeffrey A.
Accurate retrospective reporting of activities and symptoms has been shown to be problematic for older adults, yet standard clinical care relies on self-reports to aid in assessment and management. Our aim was to examine the relationship between self-report and sensor-based measures of activity. We administered an online activity survey to participants in our ongoing longitudinal study of in-home ubiquitous monitoring. We found a wide range of accuracies when comparing self-report with time-stamped sensor-based data. Of the 95 participants who completed the 2-hr activity log, nearly one quarter did not complete the task in a way that could potentially be compared with sensor data. Where comparisons were possible, agreement between self-reported and sensor-based activity was achieved by a minority of participants. The findings suggest that capture of real-time events with unobtrusive activity monitoring may be a more reliable approach to describing behavioral patterns and meaningful changes in older adults.